Theatrical Training Marked by Popular Education and Popular Culture:: a means of emancipation for young people - Camargos, Júlia (Revista Brasileira de Estudos da Presença, 2023)
The article discusses the meanings that young people from peripheral neighborhoods attribute to their theater studying experience marked by popular education and popular culture in an educational institution in Belo Horizonte. Highlighting the presence of diversity, collectivity and political agendas in their studying, young people point out social awareness as a significant impact of this process. The theatrical artistic-pedagogical experience was configured as a space for socialization, positivation of subaltern young people’s identities and contributed to their emancipation processes as social subjects.